MR Imaging Features in Marinesco-Sjögren Syndrome: Severe Cerebellar Atrophy Is Not an Obligatory Finding - Reinhold, Anke; Scheer, Ianina; Lehmann, Rüdiger; Neumann, Luitgard M.; Michael, Theodor; Varon, Raymonda; von Moers, Arpad (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Cerebellar atrophy is considered the most prominent neuroradiologic finding in Marinesco-Sjögren syndrome (MSS). Our purpose was to investigate this neuroradiologic feature in a series of patients with MSS.METHODS: Five patients with MSS (age range, 5–19 years) underwent native MR imaging of the brain. The findings were assessed with particular attention to the cerebellum and the supratentorial structures.RESULTS: Only two patients had slight cerebellar atrophy; the cerebellum was normal in size and configuration in the other patients. Additional supratentorial findings were present in some of the patients, with an apparently small anterior pituitary gland in two and the absence of the posterior pituitary bright spot in three of the patients.CONCLUSION: Cerebellar atrophy is not an obligatory finding in MSS, and almost normal cranial MR imaging results are compatible with the diagnosis. Morphologic changes of the pituitary gland seem to be common in patients with MSS and are not associated with endocrine dysfunction.